2020
DOI: 10.47222/2526-3544.rbto34432
|View full text |Cite
|
Sign up to set email alerts
|

Terapia Ocupacional Social: reflexões e possibilidades de atuação durante a pandemia da Covid-19/Social Occupational Therapy - reflections and possibilities for action the COVID-19 pandemic

Abstract: A crise sanitária pela pandemia da CoVid-19 tem demonstrado que a desigualdade social é fator determinante na circulação do vírus e no agravamento das condições de vida. Isso convocou terapeutas ocupacionais a (re)pensar estratégias de trabalho diante da reconfiguração dos cotidianos. A Rede Metuia tem atuado com grupos em situação de vulnerabilidade social e junto a demandas em contextos de interculturalidade, que envolvem a articulação individual/singular, sociocomunitária e política. Tais experiências levam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Pesquisas e acompanhamentos singulares de estudantes PRÉ-PEC-G identificaram a falta de experiência dos jovens em cozinhar seus próprios alimentos, além de repercussões financeiras diante da pandemia e as diferenças culturais no modo de se alimentar. A mediação para o acesso ao auxílio emergencial foi fundamental em algumas situações frente à falta de uma política de proteção específica (Pereira et al, 2022).…”
Section: Impactos Da Pandemia No Contexto Da Mobilidade Humana E Na E...unclassified
“…Pesquisas e acompanhamentos singulares de estudantes PRÉ-PEC-G identificaram a falta de experiência dos jovens em cozinhar seus próprios alimentos, além de repercussões financeiras diante da pandemia e as diferenças culturais no modo de se alimentar. A mediação para o acesso ao auxílio emergencial foi fundamental em algumas situações frente à falta de uma política de proteção específica (Pereira et al, 2022).…”
Section: Impactos Da Pandemia No Contexto Da Mobilidade Humana E Na E...unclassified
“…Unique research and monitoring of PRE-PEC-G students identified young people's lack of experience in cooking their own food, in addition to financial repercussions in the face of the pandemic and cultural differences in the way of eating. Mediation for access to emergency assistance was fundamental in some situations due to the lack of a specific protection policy (Pereira et al, 2022).…”
Section: Impacts Of the Pandemic In The Context Of Human Mobility And...mentioning
confidence: 99%
“…The study by Pereira et al 40 describes a strategy created by students and professionals in occupational therapy during the pandemic, which aimed to provide social support for these groups, not only in this moment of social isolation, but also for after the pandemic. This involved socio-educational support for children and youth in communities via distance learning, promoting the strengthening of socio-community ties and assisting the organization of collecting and donating basic supplies to poor communities in various regions of Brazil.…”
Section: Scientific Articlementioning
confidence: 99%